STUDENT SATISFACTION TO LECTURER PERFORMANCE IN LEARNING IN STUDY DEPARTMENT AND PROGRAM IN SCOPE OF KUPANG HEALTH POLYTECHNIC IN YEAR 2014. - YULIANA DAFROYATI (JURNAL INFO KESEHATAN, 2016)
Students, as users of educational services hope that the faculty in providing educational services running optimally due to the use of the methods of variation in the learning process, be present on time, finishing materials on time according to the syllabus, the implementation of central semester test / final examination semester timely, and return the answer sheet to students. This study aims to determine the level of satisfaction on the performance of students in the learning process Lecturer at the Polytechnic of the Ministry of Health Scope of Kupang. Respondents in this study were all students with quota sampling for all courses/study programs. Research results through descriptive analysis to know that all students feel satisfaction on the performance of lecturers in view of the five dimensions: tangible, reliability, responsiveness, assurance and empathy.